Case report: VA-ECMO for fulminant myocarditis in an infant with acute COVID-19 - Hsu, Hao-Ting; Kuo, Ni-Chun; Chen, Po-Yen; Jan, Sheng-Ling (Frontiers in Pediatrics, 2023)
Fulminant myocarditis in children was rare during the coronavirus disease 2019 pandemic, but it had the potential for high morbidity and mortality. We describe the clinical course of a previously healthy 9-month-old young male infant who rapidly deteriorated into cardiogenic shock due to coronavirus disease 2019-related fulminant myocarditis. He developed severe heart failure and multiple organ dysfunction syndrome that were treated promptly with central venoarterial extracorporeal membrane oxygenation and continuous venovenous hemofiltration. He made a good recovery without significant morbidity.